Religiosity and Occupational Well-Being Among Kindergarten Teachers: The Mediating Role of Mindfulness in Advancing SDG 3 - Lely Ika Mariyati; Eko Hardi Ansyah; Nazri Abdul Rahman; Ilham Nazhir Akbar; Sirril Wafa (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
This study explores the influence of religiosity and mindfulness on the occupational well-being of early childhood education teachers in Indonesia, with a focus on the mediating role of mindfulness. While previous research has examined religiosity and mindfulness in isolation, few have investigated their combined effect on occupational well-being, particularly within non-Western early childhood education contexts. Using a quantitative correlational design, data were collected from 118 kindergarten teachers at Aisyiyah institutions in Sidoarjo. Three adapted instruments were employed: a religiosity scale based on Glock and Stark's model, the Toronto Mindfulness Scale, and the Tripartite Occupational Well-being Scale. Results of Pearson correlation analysis showed significant positive relationships among religiosity, mindfulness, and occupational well-being. Structural equation modeling confirmed that mindfulness partially mediated the relationship between religiosity and occupational well-being. These findings suggest that both religiosity and mindfulness contribute meaningfully to teacher well-being and can serve as protective psychological resources in demanding professional environments. The study highlights the importance of culturally rooted psychological factors and supports efforts to promote teacher well-being in line with the United Nations Sustainable Development Goal 3. Future research is encouraged to examine other relevant variables, such as self-efficacy and emotional intelligence, to broaden understanding of what shapes occupational well-being in early childhood educators.